Toxicity of antimony in housefly after whole-life-cycle exposure: Changes in growth, development, redox homeostasis, mitochondrial function, and fecundity - Yuming Zhang; Jinghua Lv; Xiaoli Sun; Yiwen Zhang; Menghua Shao; Bingbing Shi; Yajie Zhang; Jihai Gu; Chenchen Zhao; Fengsong Liu (Ecotoxicology and Environmental Safety)
The increasing utilization of antimony (Sb) in manufacturing industries has led to the emergence of Sb contamination in the environment as a significant public health concern. To elucidate the toxicity of Sb and its mechanism of action, this study aimed to investigate the adverse effects of Sb on a cosmopolitan insect, housefly (Musca domestica), under a whole life cycle (from embryonic to adult stage) exposure through the examination of a suite of parameters, including biological, physiological, behavioral, and molecular endpoints. A range of Sb concentrations, including moderate contamination (0.07 mM), heavy contamination (0.7 mM), and extreme contamination (7 and 70 mM), were conducted in the study. The results indicated that the houseflies could maintain their health when exposed to 0.07 mM Sb. The exposure of Sb (0.7–70 mM) to houseflies resulted in a range of adverse effects, including developmental retardation, locomotor inhibition, gut damage, oxidative stress, and mitochondrial dysfunction in the houseflies. Significantly, Sb demonstrated reproductive toxicity in the houseflies, as evidenced by reduced reproductive capacity, DNA damage, and ovarian abnormalities. The disturbance of hormonal synthesis and the MAPK pathway induced by Sb treatment may contribute to reproductive toxicity. These comprehensive toxicological data provide insight into the prediction of toxicity and the assessment of the ecological risk of Sb.